Effect of solvent gradient inside the entropic trap on polymer migration - Mohanta D.; Giri D.; Kumar S. (My University, 2025)
By employing the exact enumeration technique on the lattice model of a polymer, we study the migration of the polymer chain across an entropic trap in a quasiequilibrium condition and explore the effect of solvent gradient present in the entropic trap which acts both parallel and perpendicular to the direction of migration. The Fokker-Planck formalism utilizes the free energy landscape of a polymer chain across the channel in the presence of the entropic trap to calculate the migration time. It is revealed that the migration is fast when the solvent gradient acts along the migration axis (i.e., x axis) inside the channel in comparison to the channel having the entropic trap. We report here for the first time that the entropic trap makes the migration faster at a certain value of solvent gradient. We also study the effect of transverse solvent gradient (along the y axis) inside the trap and investigate the structural changes of the polymer during migration through the channel. We observe the nonmonotonic dependence of migration time on the solvent gradient. © 2022 American Physical Society.